2003
DOI: 10.1038/sj.bjc.6600917
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the time course and prognostic factors determining toxicity due to infused fluorouracil

Abstract: This study used a prospectively managed clinical database in order to identify 1470 patients with gastrointestinal cancers receiving protracted venous infusion (PVI) fluorouracil (5FU). It aimed to determine the time course of toxicity due to PVI 5FU and to analyse factors predicting toxicity. The initial development of stomatitis occurred more rapidly than diarrhoea or palmar plantar erythema (PPE). The percentage of patients with National Cancer Institute Common Toxicity Criteria (CTC) grade 2 or worse PPE p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…The other major factor likely to result in failure to complete chemotherapy is toxicity. It is well-documented that bolus schedules of 5FU cause more severe leucopenia and stomatitis in elderly patients, particularly in females (Milano et al, 1992;Metaanalysis Group in Cancer, 1998;Zalcberg et al, 1998;Popescu et al, 1999;Tebbutt et al, 2000;Sloan et al, 2002;Chansky et al, 2005). In agreement with these findings, the present study found that females were less likely to complete adjuvant chemotherapy when adjusted for other variables (Table 6), and we postulate this is due to an increased incidence of toxicity.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The other major factor likely to result in failure to complete chemotherapy is toxicity. It is well-documented that bolus schedules of 5FU cause more severe leucopenia and stomatitis in elderly patients, particularly in females (Milano et al, 1992;Metaanalysis Group in Cancer, 1998;Zalcberg et al, 1998;Popescu et al, 1999;Tebbutt et al, 2000;Sloan et al, 2002;Chansky et al, 2005). In agreement with these findings, the present study found that females were less likely to complete adjuvant chemotherapy when adjusted for other variables (Table 6), and we postulate this is due to an increased incidence of toxicity.…”
Section: Discussionsupporting
confidence: 90%
“…Many of the toxicities that lead to the termination of 5FU chemotherapy culminate around the time of the third cycle (Tebbutt et al, 2000). Unfortunately, steady-state plasma 5FU levels do not correlate with toxicity (Jodrell et al, 2001) and hence pharmacokinetic monitoring is not used to identify patients who are at increased risk of toxicity (Tebbutt et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggested that women might be intrinsically more sensitive to 5-FU. However, this gender difference in toxicity is not limited to bolus 5-FU/LV schedules, but also extends to infused 5-FU (Tebbutt et al, 2003). In our analysis, we evaluated whether there were gender differences in efficacy and developing toxicity to irinotecan.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in the event of marked DPD deficiency, one could anticipate intracellular metabolic imbalance with intracellular overexposure to locally produced 5-FU within normal proliferating cells. Women are at risk of severe toxicity under fluoropyrimidines (33). Prospective studies have shown that women exhibit lower DPD activity than men (24).…”
Section: Discussionmentioning
confidence: 99%